In Situ Three‐Dimensional Observation of Perovskite Crystallization Revealed by Two‐Photon Fluorescence Imaging. Issue 13 (18th April 2022) - Yang, Wenkai; Liu, Lige; Dong, Dashan; Gao, Yunan; Yang, Hong; Gong, Qihuang; Shi, Kebin
Abstract: Understanding in situ crystallization of perovskite materials is fundamentally important for perovskite‐based materials, components, and devices. Here, in situ crystallization of perovskites in three dimensions is investigated using two‐photon excitation fluorescence microscopy with diffraction‐limited spatial resolution. By taking a perovskite precursor droplet as an example, the spatiotemporal kinetics of nanocrystal formation during crystallization is demonstrated, taking advantage of the perovskites' unique advantage of in situ synthesis from solutions. Based on the time‐lapsed 3D two‐photon excitation fluorescence imaging, the in situ formation of the "crystal crust" is observed and the results suggest a centripetal direction of the crystallization starting from the free surface of the droplet. Analysis based on fluorescence intensity further confirms the evaporation kinetics in a sessile precursor droplet. The reported results demonstrate a promising framework for utilizing two‐photon excitation fluorescence microscopy as a powerful tool to study the in situ crystallization of perovskite materials as well as more general fluorescence‐related chemical reactions in three dimensions. Abstract : In situ crystallization of perovskites in three dimensions is investigated using two‐photon excitation fluorescence microscopy. The spatiotemporal kinetics of nanocrystal formation during crystallization is demonstrated and the in situ formation of the "crystal crust" is observed, which suggests a centripetal direction of the crystallization starting from the free surface of the droplet.